2018
DOI: 10.1016/j.toxicon.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Female-biased population divergence in the venom of the Hentz striped scorpion (Centruroides hentzi)

Abstract: Sex-biased genes are expressed at higher levels in one sex and contribute to phenotypic differences between males and females, as well as overall phenotypic variation within and among populations. Venom has evolved primarily for predation and defense, making venom expression a highly variable phenotype as a result of local adaptation. Several scorpion species have shown both intraspecific and intersexual venom variation, and males have been observed using venom in courtship and mating, suggesting the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…Specifically, females contribute more significantly to the variation of venom between populations. In contrast, within-population venom variation is mostly driven by differences in the venom profile of males [123]. This variation within and among populations is likely contributed in part to sexspecific venom differences.…”
Section: Intersexual Variation Of Toxin Expressionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, females contribute more significantly to the variation of venom between populations. In contrast, within-population venom variation is mostly driven by differences in the venom profile of males [123]. This variation within and among populations is likely contributed in part to sexspecific venom differences.…”
Section: Intersexual Variation Of Toxin Expressionmentioning
confidence: 95%
“…The venom profile of the Hentz striped scorpion (Centruroides hentzi) revealed significant intersexual variation within and among populations [123]. Specifically, females contribute more significantly to the variation of venom between populations.…”
Section: Intersexual Variation Of Toxin Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual variation of venom composition has been documented for a few taxa, principally spiders, scorpions, snakes, and a species of fish [122,123,124,125]. Research on Thalassophyrne maculosa (cano toadfish) showed that male venom had double the protein content of that of females and differing bioactivities, with males having a greater target affinity to nociceptors whilst females had greater proteolytic activity [123].…”
Section: Intersexual Variation In Venommentioning
confidence: 99%
“…transcriptomic study of a non-buthid scorpion belonging to the family Vaejovidae (Cid-Uribe et al, 2018) and Ward et al examines sex-related differences in the venom composition of the Hentz striped scorpion (Ward et al, 2018a). The remaining reviews do not focus on specific arthropod lineages, but rather provide a general overview of the biochemistry and evolution of arthropod venoms (Laxme et al, 2018) or the structural diversity of arthropod toxins (Daly and Wilson, 2018).…”
Section: Content Of This Special Toxicon Issue On Arthropod Venomsmentioning
confidence: 99%